How public libraries build sustainable communities in the 21st century - Williams-Cockfield, Kaurri C.; Mehra, Bharat (Emerald Publishing Limited, 2023)
Public libraries, through their mission, vision, and position in the community, play a significant part in building community sustainability and are already positioned to serve as a "backbone support organization" for collective impact initiatives. However, their efforts are often unrecognized by local governments and other social justice organizations. How Public Libraries Build Sustainable Communities in the 21st Century, through research, case studies, and personal narratives representing both national and international perspectives, examines the capacity of public libraries to impact social change at the community level. The overarching goal is to change the narrative with community stakeholders by presenting illustrative examples of how public libraries are driving community change and how these efforts align with the UN SDGs.
Keywords: Libraries and community.; Public libraries -- Social aspects.; Sustainable development.; Language Arts & Disciplines -- Library & Information Science -- General.; Public libraries.; elektronické knihy; electronic books